Horizontal, but not vertical, biotic interactions affect fine‐scale plant distribution patterns in a low‐energy system. Issue 3 (1st March 2013) - le Roux, Peter C.; Lenoir, Jonathan; Pellissier, Loïc; Wisz, Mary S.; Luoto, Miska
Abstract : Studies of species range determinants have traditionally focused on abiotic variables (typically climatic conditions), and therefore the recent explicit consideration of biotic interactions represents an important advance in the field. While these studies clearly support the role of biotic interactions in shaping species distributions, most examine only the influence of a single species and/or a single interaction, failing to account for species being subject to multiple concurrent interactions. By fitting species distribution models (SDMs), we examine the influence of multiple vertical (i.e., grazing, trampling, and manuring by mammalian herbivores) and horizontal (i.e., competition and facilitation; estimated from the cover of dominant plant species) interspecific interactions on the occurrence and cover of 41 alpine tundra plant species. Adding plant–plant interactions to baseline SDMs (using five field‐quantified abiotic variables) significantly improved models' predictive power for independent data, while herbivore‐related variables had only a weak influence. Overall, abiotic variables had the strongest individual contributions to the distribution of alpine tundra plants, with the importance of horizontal interaction variables exceeding that of vertical interaction variables. These results were consistent across three modeling techniques, for both species occurrence and cover, demonstrating the pattern to be robust. Thus, the explicit consideration of multiple biotic interactions reveals that plant–plant interactions exert control over the fine‐scale distribution of vascular species that is comparable to abiotic drivers and considerably stronger than herbivores in this low‐energy system.